Analisis Rasio Profitabilitas Untuk Menilai Kinerja Keuangan Pada PT. Semen Indonesia (Persero) Tbk Tahun 2016-2020 - Abigael Tandi Kapang; Jemi Pabisangan Tahirs (Jurnal Riset Ekonomi dan Akuntansi, 2023)
Financial performance is a unit of analysis carried out with the aim of finding out the extent to which the company has implemented the rules in implementing finances properly and correctly. The aim of this research is to determine the financial performance of PT Semen Indonesia (Persero) Tbk based on the results of profitability ratio calculations. The research method is research using quantitative descriptive methods. The data used in this research is secondary data in the form of the financial reports of PT Semen Indonesia (Persero) Tbk. The data analysis technique in this research uses measuring tools in the form of Net Profit Margin (NPM), Return On Assets (ROA), and Return On Equity (ROE) ratios. The results of the research show that the average value of the profitability ratio of PT Semen Indonesia (Persero) Tbk is in very poor criteria, so that the financial performance of PT Semen Indonesia (Persero) Tbk is considered to be still very poor because the three ratios show very poor values and do not meet industry standards.